MEASURING EFFICIENCY OF BROILER BREEDING PROJECTS USING STOCHASTIC COST LIMIT IN IRAQ (BAGHDAD GOVERNORATE) - R.T. Al-Wasity; Z. H. Mahmood; M. H. AL-Sammarraie (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The study aimed to estimate the cost efficiency and to know the most important social and economic factors affecting the production of broiler chickens in the Baghdad governorate. Using the random parametric analysis (SFA) based on the greatest possibility (ML) method. To determine the factors affecting the cost inefficiency function. The study relied on primary data from its field sources according to a questionnaire prepared for this purpose in Baghdad Governorate for one production year (2022). Data were collected randomly from (64) projects out of a total of (546) projects, with a rate of (11.72%). The results indicated that all the explanatory variables confirmed a prior prediction of the economic theory, as all the coefficients estimated for the cost of fodder, chicks, medicines, vaccines, and chicken meat production gave positive parameters indicating agreement with the assumption that the cost function increases directly with the input prices. The average cost of broiler breeding projects in the sample area was estimated at 1.04, which is about 4% more than the minimum cost set by the limits. Breeders can achieve an additional profit of up to 12.2% if the optimum efficiency is reached, so breeders must develop their agricultural skills in managing the use of inputs to achieve the lowest possible cost efficiency.